Penerapan Sistem Informasi Akuntansi dalam Pengelolaan Keuangan pada UMKM Wingko Bunda di Tulungagung - Alfionita, Yesica Lety; Estiningrum, Sri Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Small and medium enterprises (SMEs) currently play an important role in Indonesia's economic growth. Many small and medium-sized enterprises (SMEs) still manually document financial transactions and prepare financial reports for their organizations at this point in history. The purpose of this research is to assist in the development of an accounting information system for small and medium enterprises. This finding is based on the original research data collected at Wingko Bunda SMEs directly from the field or research location. Researchers used inductive data analysis techniques and collected data from one source. The results of qualitative research are the result of this approach. Researchers found that a computer-based system can make the data storage process more effective, fast and accurate for SMEs owners to use in making decisions about their company, according to research findings.